Tanzania Dar es Salaam city profile - Kithakye, David; UN-HABITAT (Nairobi UNON, 2009)
The Urban Profiling is an accelerated and actionoriented urban assessment of needs and capacitybuilding gaps at local and national levels. It is currently being implemented in over 20 countries in Africa and Arab States. RUSPS uses a structured approach where priority interventions are agreed upon through consultative processes. The RUSPS methodology consists of three phases: (1) a rapid participatory urban profiling, at national and local levels, focusing on Governance, Slums, Gender, HIV/AIDS, and Environment, and proposed interventions; (2) detailed priority proposals; and (3) project implementation. Urban Profiling in Tanzania encompasses a national profile, as well as profiles for Bagamoyo, Dar es Salaam, and Morogoro, each published as a separate report. This is the Dar es Salaam report and it constitutes a general background, a synthesis of the four themes ? Governance, Slums, Gender and HIV/AIDS, and Environment ?, and priority project proposals.
Includes Bibliography
Keywords: Governance, Slums Gender and HIV/AIDS Enviroment